H3PW12O40: An Efficient Catalyst for the Synthesis of Spirooxindoles Under Ultrasound Irradiation - Samadizadeh, Marjaneh (Asian Journal of Chemistry, 2013)
A simple and efficient one-pot three-component synthesis of the biologically important spirooxindoles scaffold was carried out by the reaction of isatin, malononitrile and 1,3-dicarbonyl compounds in presence of tungstophosphoric acid as a catalyst. This method is of great value because of high yield processing and easy handling.